International investment - Gilbert, Robert A. (New York : Simmons-Boardman Pub. Corp., 1963)
The book seeks to describe the how's and the why's of foreign investment. The treatment provides an outline of the theoretical background of investing abroad as well as practical specific details. In illustrating the basic principles and problems involved, individual countries and specific geographical areas have been selected.
Includes index
usc 16/07/2018
Loans
Keywords: Investments, American; Investments, International